Theatre caption presentation system for both hearing impaired and unimpaired. (2015) - Konya, Yuko; Siio, Itiro
This study proposes a caption-presentation system that enables both the hearing-impaired and unimpaired to simultaneously enjoy theatrical performance. In present day Japan, few theatres employ programs that provide captions for the hearing impaired. The programs that do provide captions only show dialogue and sound (musical note icons), not audience response, which is one of the most important factors in enjoying plays. A majority of the captions that are displayed are set on the outside of the stage; therefore, it is difficult to determine which performer is speaking. To address these issues, we propose, implement and evaluate caption-presentation methods for the hearing impaired, which include support for dialogue, sound effects and audience response. We apply the caption-presentation system to an actual performance held in a theatre. We improve the proposed system based on director feedback, stage structure limitations and interview results about the previous system.